2021
DOI: 10.20892/j.issn.2095-3941.2020.0728
|View full text |Cite
|
Sign up to set email alerts
|

Somatic copy number alterations are predictive of progression-free survival in patients with lung adenocarcinoma undergoing radiotherapy

Abstract: Objective: Lung cancer is the most common cause of cancer-related deaths worldwide. Somatic copy number alterations (SCNAs) have been used to predict responses to therapies in many cancers, including lung cancer. However, little is known about whether they are predictive of radiotherapy outcomes. We aimed to understand the prognostic value and biological functions of SCNAs. Methods: We analyzed the correlation between SCNAs and clinical outcomes in The Cancer Genome Atlas data for 486 patients with non-small c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…TMB is associated with response to immunotherapy [ 10 ]. In NSCLC and melanoma, high SCNA was associated with poorer patient survival, and SCNA levels were a better predictor of survival in patients [ 11 , 12 ]. Davoli et al found that most of the gene expression signatures with significant downregulation in high SCNA tumors were signatures related to immune cells including CD4 + T cells, CD8 + T cells, macrophages, dendritic cells (DC), and natural killer (NK) cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…TMB is associated with response to immunotherapy [ 10 ]. In NSCLC and melanoma, high SCNA was associated with poorer patient survival, and SCNA levels were a better predictor of survival in patients [ 11 , 12 ]. Davoli et al found that most of the gene expression signatures with significant downregulation in high SCNA tumors were signatures related to immune cells including CD4 + T cells, CD8 + T cells, macrophages, dendritic cells (DC), and natural killer (NK) cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%